Inventory management systems of Anwar Jute Spinning Mills Ltd. in Bangladesh - Huda, Md. Nurul (BRAC University, 2016)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2015.